Crop Coefficients of Paddy and Evapotranspiration in the Minapadi Model System Applying Nonpowered Automatic Fertigation - Tri Julianto, Baskoro; Setiawan, Budi Indra; Saptomo, Satyanto Krido; Liyantono; Kurniawati, Euis Kania (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
In irrigation and agricultural planning, the crop coefficient value plays an important role in calculating water planning on land. This study aims to calculate the crop coefficient (Kc) of rice in a Nonpowered Automatic Fertigation (FONi) irrigation system combined with a minapadi system as a reference for irrigation planning. This study was conducted experimentally for 99 days in Dramaga, Bogor, using the FONi Minapadi system consisting of a fiberglass tank, a water supply tank, and an automatic float to maintain the water level. Actual evapotranspiration (ETa) data were calculated based on water balance, while potential evapotranspiration (ETo) was modeled using five methods: Penman-Monteith, Turc, Hargreaves, Makkink, and Blaney-Criddle. Model validation was performed using linear regression against the Penman-Monteith method as the standard reference. The results show that the total ETa during the observation period was 421.93 mm. Among the ETo calculation methods, the Turc model provided results closest to the Penman-Monteith method, with a coefficient of determination (R²) of 0.741 and the lowest sum of squares error (SSE) of 56.026. The calculated Kc values varied throughout the rice growth phase, with the highest value of 1.84 observed during the reproductive phase. The relatively high Kc value reflects significant water demand in the FONi Minapadi system, influenced by system characteristics and environmental conditions. This study concludes that the FONi Minapadi system has the potential to improve irrigation management efficiency in integrated agriculture. However, further research is needed to understand the influence of technical and environmental factors on the Kc value and to compare it with other irrigation systems.